1987
DOI: 10.1016/0044-8486(87)90062-7
|View full text |Cite
|
Sign up to set email alerts
|

Steroidogenesis in the testes and seminal vesicles of spawning and non-spawning African catfish, Clarias gariepinus

Abstract: The in vitro biosynthesis of steroids was studied in testes as well as seminal vesicles of nonspawning pond and spawning feral African catfish, collected during the breeding season. In testes of non-spawners the conversion of [3H]-pregnenolone was directed towards 11-oxygenated androgens and 5j?-pregnane-3cu,l7cu,20cz-triol, whereas in testes of spawners the production of progesterone and 17&-hydroxyprogesterone prevailed. The seminal vesicles, on the other hand, produced mainly pregnenolone ester, androstened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Hormonal injection usually results in a sequence of steroid secretion; in C. batrachus hCG induces first a peak of secretion in the blood of testosterone (and I I KT) followed by progestins and again 11 KT (Zairin et al, 1993). ln C. gariepinus exhibiting spontaneous spermiation the production of testosterone glucuronide was considerably enhanced (Resink et al, 1987a) and 5 f3 reduced steroids were found in spawning fish but not in non-spawning individuals (Schoonen et al, 1987). After in vitro incubation, testis of S. glanis stimulated by carp pituitary homogenates produced 20 a: Progesterone, 17 a20/3 Progesterone and l1 (1 hydroxyprogesterone (Kime et al, 1993).…”
Section: Malementioning
confidence: 94%
“…Hormonal injection usually results in a sequence of steroid secretion; in C. batrachus hCG induces first a peak of secretion in the blood of testosterone (and I I KT) followed by progestins and again 11 KT (Zairin et al, 1993). ln C. gariepinus exhibiting spontaneous spermiation the production of testosterone glucuronide was considerably enhanced (Resink et al, 1987a) and 5 f3 reduced steroids were found in spawning fish but not in non-spawning individuals (Schoonen et al, 1987). After in vitro incubation, testis of S. glanis stimulated by carp pituitary homogenates produced 20 a: Progesterone, 17 a20/3 Progesterone and l1 (1 hydroxyprogesterone (Kime et al, 1993).…”
Section: Malementioning
confidence: 94%
“…In the African catfish the seminal vesicle has been shown to attract female conspecifics after ovulation (Resink et al, 1987a). The seminal vesicle fluid contains water-soluble steroid conjugates (Schoonen et al, 1987a). This means that such steroid conjugates may be involved in the sex attracting function of the seminal vesicles.…”
Section: After Treatment Of Hypophysectionizedmentioning
confidence: 99%
“…This has been confirmed by enzyme histochemical studies (Van Den Hurk et al, 1987a,b). Recent gas chromatography-mass spectrometry analysis of the seminal vesicle fluid showed the presence of different steroid glucuronides (Schoonen et al, 1987). Secretion of the seminal vesicle fluid takes place via the sperm duct (Van Den Hurk et al, 1987b).…”
Section: Introductionmentioning
confidence: 99%